Accelerating employee-related scholarship in service management: Research streams, propositions, and commentaries. (3rd October 2017) - Subramony, Mahesh; Ehrhart, Karen; Groth, Markus; Holtom, Brooks C.; van Jaarsveld, Danielle D.; Yagil, Dana; Darabi, Tiffany; Walker, David; Bowen, David E.; Fisk, Raymond P.; Grönroos, Christian; Wirtz, Jochen
Abstract : Purpose: The purpose of this paper is to accelerate research related to the employee-facets of service management by summarizing current developments in multiple research streams, providing propositions, and articulating new directions for theory and empirical inquiry. Design/methodology/approach: Seven scholars provide short reviews of the core topics and findings from four employee-related research streams – collective turnover, service climate, emotional labor, and occupational stress; and generate propositions to guide future theoretical and empirical work. Four distinguished service scholars – David Bowen, Ray Fisk, Christian Grönroos, and Jochen Wirtz comment upon these research streams and provide future directions for accelerating employee-related research in service management. Findings: All four research-streams yield insights that have the potential to advance service management research. Commentaries from the distinguished scholars further integrate this work with key concerns within service management including technology-enablement, transformative services, and service strategy. Originality/value: This paper is unique in its scope of coverage of management topics related to service and its aim to promote interdisciplinary dialog between service management scholars and researchers conducting employee-related research relevant to services.